Self‐certification versus physician certification of sick leave for reducing sickness absence and associated costs - Kausto, Johanna (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effects of introducing, abolishing, or changing the period of self‐certification of sickness absence on: 1. the total or average duration (number of sickness absence days) of short‐term sickness absence periods; 2. the total or average number of short‐term sickness absence periods; 3. the associated costs (of sickness absence and (occupational) health care); and 4. social climate, supervisor involvement, and work load or presenteeism (Figure 1).